The role of cytokines in wound healing: from mechanistic insights to therapeutic applications - Rachel Si-Yin Wong; Timothy Tan; Alexander Shao-Rong Pang; Dinesh Kumar Srinivasan (Exploration of Immunology)
Wound healing is an area of growing importance in the healthcare field, especially chronic wounds associated with comorbidities like diabetes mellitus (DM), hypoxic stress, obesity, and malnutrition. Chronic wounds significantly increase healthcare costs and reduce patients’ quality of life. Cytokines are a promising therapeutic target, as they regulate all stages of wound healing, and dysfunction in cytokine production can cause inflammatory non-healing wounds. Interleukin-1 (IL-1), IL-2, IL-6, IL-8, and tumour necrosis factor-α (TNF-α) facilitate leukocyte recruitment and clear dead cells during the initial inflammation stage while transforming growth factor-β (TGF-β), IL-4, and IL-13 inhibit inflammation and stimulate proliferation of fibroblasts to begin extracellular matrix (ECM) deposition. Given the complexity of cytokine interactions and their diverse cellular targets, a comprehensive understanding of these signaling pathways is crucial. This review examines the multifaceted roles of cytokines in wound healing and discusses recent advancements in the therapeutic application of cytokine modulation for improved wound care outcomes. Despite significant advancements in improving the specificity of cytokine therapies, further research is needed to focus on targeting downstream signaling pathways or specific receptors to minimize the adverse effects associated with these treatments.